2018
DOI: 10.1038/s41598-018-25092-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rural-urban environment on metabolic profile and response to a 5-day high-fat diet

Abstract: Epidemiological studies have indicated that rural living might be protective against type 2 diabetes development. We compared the metabolic profile and response to a short-term high-fat high-calorie diet (HFD) of men with the same genetic background living in an urban and rural area of Indonesia. First, we recruited 154 Floresian male subjects (18–65 years old), of whom 105 lived in a rural area (Flores) and 49 had migrated and lived in urban area (Jakarta) for more than 1 year. The urban group had significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…Fourth, it must be noted that the SUGARSPIN study population represents an Indonesian population living in rural areas of Indonesia, hence results from this present study may need to be confirmed in the urban Indonesian population. However, a previous study had observed that adiponectin concentrations were not different between urban and rural Indonesians, which may support the generalizability of our results to the greater Indonesian population [40]. Fifth, We included different age groups for the two populations (aged >18 in the Indonesian population, aged 45e65 in the Dutch population).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Fourth, it must be noted that the SUGARSPIN study population represents an Indonesian population living in rural areas of Indonesia, hence results from this present study may need to be confirmed in the urban Indonesian population. However, a previous study had observed that adiponectin concentrations were not different between urban and rural Indonesians, which may support the generalizability of our results to the greater Indonesian population [40]. Fifth, We included different age groups for the two populations (aged >18 in the Indonesian population, aged 45e65 in the Dutch population).…”
Section: Discussionsupporting
confidence: 70%
“…The interand intra-assay coefficients of variance (CV) of leptin were 2.2% and 3.2%. While for adiponectin, the inter-and intraassay CV were 3.1% and 7.0%, respectively [40].…”
Section: Assessment Of Leptin and Adiponectin Concentrationsmentioning
confidence: 94%
“…The higher-level functional pathways related to carbohydrate, protein and lipid metabolism were also found to be significantly associated with the rural location compared to urban slum location. These differences could be attributed to migration from rural to urban settings which has been previously reported to impair metabolic pathways (62) and gut microbiome composition (63,64). Although, the gut microbiome has been shown to affect the metabolism of macronutrients with the help of enzymes such as of CAZymes, deaminases, lipases, and others maintaining the homeostasis of metabolic pathways (65), however, the causal factors contributing to this remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have evaluated the impact of urbanization on insulin resistance in varied locations across the globe. A higher prevalence of insulin resistance was identified in Floresian men (a specific ethnic group in Indonesia) that had moved to an urban center (Jakarta) compared to men than remained in the rural area [39]. Similarly, another study revealed statistically significant higher HOMA-IR in Ghanaian adults living in urban areas compared to rural areas [40].…”
Section: Discussionmentioning
confidence: 99%